Pembudayaan etika dan penyelesaian konflik dalam kalangan agen pembangunan di Kelantan - Suhana binti Saad; Suraiya binti Ishak (Universiti Kebangsaan Malaysia, 2010)
In general, Malaysia is still faced with blatant development disparity within states, region and urban-suburban. The National Mission of the Ninth Malaysia Plan (2006-2010) and the National Integrity Plan (2004) has focused on the development parity as one of the main agenda of the country. Hence, one of the main challenges is to strengthen the integrity of federal-state development agents and all parties involved in the economic and political governance of the country. This article focuses on the political-economic development scenario in Kelantan to discuss the ethical issues embedded in the federal-state relationship and the weaknesses of the existing delivery system. Secondary reports such as the state and the country’s official reports are used as the main sources in discussing the issue. Agency theory is used to describe the relationship that exists between the federal-state agents. This is because the citizens are the principles, who had delegated the authority to administer the resources owned by the country and the state, to the administrator-agents at the state and national levels. As such, the state and federal administrators (politicians and government servants) would have opportunities for easy access to valuable resources, and thereby influence its distribution as well as development implementation at the grass roots level. From the discussion, it can be said that the development agents’ behaviour at the state and national levels has posed as hindrances to the development processes, that ultimately put the residual cost on the rakyat (citizens). Efforts to strengthen integrity among political agents and administrators are becoming increasingly indispensable for managing conflicts among federal-state development agents.